The effect of fermented raintree (Samanea saman) seed meal with yoghurt in feed on protein efficiency ratio and growth rate of tilapia (Oreochromis niloticus) in controlled containers - Anwar, Asni; Nurhadi, A. R.; Murni, Murni; Malik, Abdul; Soadiq, Syawaluddin; Berliana, Walda Dewi; Kamaruddin, Kamaruddin; Ayuzar, Eva (Universitas Malikussaleh, 2024)
This study aims to determine the effect of adding fermented raintree (Samanea saman) seed meal to the feed on the protein efficiency ratio and growth rate of Nile tilapia (Oreochromis niloticus). The study uses a Completely Randomized Design (CRD) consisting of 5 treatments with 3 replications. Data analysis was performed using ANOVA (analysis of variance) at a 5% significance level, followed by Duncan's test. Treatment A: non-fermented raintree seed meal (control), Treatment B: raintree seed flour fermented with 4 mL/100g of yoghurt, Treatment C: raintree seed meal fermented with 6 mL/kg of yoghurt, Treatment D: raintree seed meal fermented with 8 mL/kg of yoghurt, and Treatment E: raintree seed meal fermented with 10 mL/kg of yoghurt. The main parameters observed were protein efficiency ratio and daily growth rate in length and weight. The study results indicated that the addition of fermented raintree seed meal in the feed showed a better protein efficiency ratio and daily growth rate in length and weight compared to the treatment without the addition of fermented raintree seed flour in the feed. The best protein efficiency ratio and daily growth rate in length and weight were obtained with the addition of 4 mL/kg of fermented raintree seed meal in the feed of Nile tilapia (O. niloticus).Keywords: Fermentation; Oreochromis niloticus; Protein efficienci ratio; Samanea saman; Yoghurt